PENGARUH EARNING PER SHARE, UNDERWRITER REPUTATION, DAN OVERSUBSCRIPTION TERHADAP TINGKAT UNDERPRICING SAHAM SAAT INITIAL PUBLIC OFFERING DI BURSA EFEK INDONESIA - Wardah Hanifah Wisudewi; Yusriyati Nur Farida; Taufik Hidayat (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, 2022)
This study aims to analyze and determine the effect of Earning Per Share, Underwriter Reputation, and Oversubscription on the level of underpricing of shares during the Initial Public Offering (IPO) on the Indonesia Stock Exchange (IDX). The theory used in this study is signal theory which reflects the relationship between management and investors in providing company information using positive and negative signals. This study uses quantitative methods to test the three hypotheses that have been formulated. The object of this research is a company that is conducting an Initial Public Offering (IPO) on the Indonesia Stock Exchange (IDX) in 2019-2021. The sample for this research was taken from 60 companies which were obtained by purposive sampling technique so that 60 sample data were obtained. The analytical method used was multiple regression analysis using SPSS version 25.0 software. Based on data analysis using multiple regression, the results of this study show that (1) earning per share has no effect on the level of underpricing, (2) underwriter reputation has no effect on the level of underpricing, (3) oversubscription has no effect on the level of underpricing. The implications obtained from this research are to increase knowledge about the factors that can affect the level of underpricing as a consideration for companies before conducting an Initial Public Offering (IPO) on the Indonesia Stock Exchange (IDX) and for investors as a basis for making investment decisions on Indonesian Stock Exchange (IDX).